The effect of substrate temperatures on the characterization of CdSe:Cu detector - E. M. N. Al-Fawadi (مجلة بغداد للعلوم)
The CdSe:Cu photoconductive detector was fabricated using vacuum technique on glass substrate at different temperatures. The effect o1’ the substrate temperatures of the prepared films upon, the structural , I-V characteristics, photoconductive properties, spectral response, quantum efficiency, NEP, gain and declivity properties of the detector was studied. The structure of the prepared films was studied using XRD. It was found that the crystal structure is improvement with increasing doping and substrate temperatures.